Bezpośrednia sprzedaż produktów rolniczych jako element rozwoju gospodarki lokalnej - Dziedzic, Sylwia (Direct Sales of Agricultural Products as An Opportunity for Polish Farmer in the Conditions of Global and Local Competitiveness, 2006)
In the paper there is presented some alternative for globalization which is a model of the local economy. There is also presented a local initiative, one from the numerous possible ones, i.e. the direct sales of agricultural products, which is an included element of every local economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 209-215